Perlindungan Hukum Kepada Konsumen dalam Perdagangan Transaksi Elektronik Berbasis Online - Saifudin, Bandaharo (Universitas Medan Area, 2019)
This paper discusses the legal protection to consumers in electronic commerce studies according to statutory provisions. The purpose of this research is to protect the law of consumers who carry out trade transactions through online electronics and the implementation of electronic commerce on the sale and purchase site of Kaskus and how to sell to avoid fraud. This research method is a normative juridical that leads to empirical research that is research conducted using material sourced from secondary data, including language from applicable legislation, books, court decisions, relevant legal theories, and opinions of bachelor. The results and discussion regarding legal protection to consumers in online-based electronic commerce (e-commerce) for conducting transactions as regulated in Article 4 letters c and h of the UUPK are absent. The right of consumers to obtain true and honest information about the conditions and guarantees of goods are not fulfilled. Fulfillment of consumer rights to obtain compensation and compensation if the goods received are not in accordance with what was promised, to get compensation by asking consumers to send the goods back to the seller and then the obligations of the business actor in this provision the seller as legally stated the seller must be responsible for returning the purchase price and reimbursing costs or losses to consumers.